2016
DOI: 10.1371/journal.pone.0160852
|View full text |Cite
|
Sign up to set email alerts
|

Are Epiphytic Microbial Communities in the Carposphere of Ripening Grape Clusters (Vitis vinifera L.) Different between Conventional, Organic, and Biodynamic Grapes?

Abstract: Using barcoded pyrosequencing fungal and bacterial communities associated with grape berry clusters (Vitis vinifera L.) obtained from conventional, organic and biodynamic vineyard plots were investigated in two subsequent years at different stages during berry ripening. The four most abundant operational taxonomic units (OTUs) based on fungal ITS data were Botrytis cinerea, Cladosporium spp., Aureobasidium pullulans and Alternaria alternata which represented 57% and 47% of the total reads in 2010 and 2011, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 48 publications
5
59
1
1
Order By: Relevance
“…In contrast to grape leaves, grape berries were less affected by agricultural management. This result supports previous studies indicating that the natural phyllosphere bacteria of the grape berry are likely to be highly resilient to agricultural treatment (Kecskeméti et al, ). Additionally, our study suggests that the sensitivity to agricultural management differs between leaf‐associated and berry‐associated bacterial communities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to grape leaves, grape berries were less affected by agricultural management. This result supports previous studies indicating that the natural phyllosphere bacteria of the grape berry are likely to be highly resilient to agricultural treatment (Kecskeméti et al, ). Additionally, our study suggests that the sensitivity to agricultural management differs between leaf‐associated and berry‐associated bacterial communities.…”
Section: Discussionsupporting
confidence: 92%
“…It is also important to the wine industry to understand how agricultural management affects the microbial community of grapevines because grapevine microorganisms can affect the production of healthy grapes (Barata, Malfeito-Ferreira, & Loureiro, 2012;Pinto & Gomes, 2016) and wine quality (Bokulich et al, 2016;Knight, Klaere, Fedrizzi, & Goddard, 2015;Mezzasalma et al, 2017). The natural phyllosphere bacteria of the grapevine are likely to be highly resilient to agricultural treatments; studies have shown that differences in management, including chemical fungicides (Perazzolli et al, 2014), biological control (Perazzolli et al, 2014), and conventional, organic and biodynamic systems (Kecskeméti, Berkelmann-Löhnertz, & Reineke, 2016), do not affect bacterial diversity indices. On the other hand, the composition of bacterial communities found on wine grapes has been shown to be affected by agricultural practices, as differences in dominant taxonomic groups between organic and conventionally managed grapes have been observed (Pinto & Gomes, 2016).…”
mentioning
confidence: 99%
“…Durand et al (2018) characterized the bacterial genera such as Methylobacterium, Kineococcus, Sphingomonas, and Hymenobacter of the phylum Firmicutes from the leaf surface. The phyllosphere of the grapevine contains Acinetobacter, Bacillus, Citrobacter, Curtobacterium, Enterobacter, Erwinia, Frigoribacterium, Methylobacterium, Pantoea, Pseudomonas, and Sphingomonas as dominant genera (Kecskeméti et al 2016). Steven et al (2018) characterized Pseudomonas and Enterobacteriaceae as predominant taxa from apple.…”
Section: Bacterial Diversity In the Phyllospherementioning
confidence: 99%
“…Steven et al (2018) characterized Pseudomonas and Enterobacteriaceae as predominant taxa from apple. Several studies revealed Pseudomonas as the most abundant genus of phyllosphere region (Aleklett et al 2014;Kecskeméti et al 2016;Steven et al 2018). Seed coat associated bacteria that have been reported in phyllosphere are mainly Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria (Johnston-Monje and Raizada 2011;Rodríguez-Escobar et al 2018).…”
Section: Bacterial Diversity In the Phyllospherementioning
confidence: 99%
“…Alternaria sp. are plant pathogens that are also commonly identified on grapes and in grape must [44,64,65]. M. tassiana , also known as Davidiella tassiana , is a common grape symbiont that has been previously isolated from vineyards [12,44,66,67], and has been identified as the most abundant fungal species isolated on grapes in one study [65].…”
Section: Resultsmentioning
confidence: 99%